CONSTRUCTION AND EXPRESSION OF RECOMBINANT Staphylococcus WL1 LIPASE - Khairunnisa, Fatiha
Lipase (EC 3.1.1.3) is an enzyme which has ability to catalyze hydrolysis reaction and synthesis of triacylglycerol. Lipase from Staphylococcus WL1 isolate (LipFWS) catalyzes the transesterification of CPO to produce biodiesel. The characteristics of LipFWS with KM value of 9.8 mM and optimum activity at 55 ?C and pH 7 are suitable for the application in biodiesel industry. In previous